Answer:B
Step-by-step explanation:
I just tried it and i got a 100
Answer:
b
Step-by-step explanation:
Answer:
a^9*b^6
Step-by-step explanation:
a^(-8) b 1 1
-------- = a^(-3), and ----------- = --------- Their product is --------------
a^(-5) b^(3) b^2 a ^3*b^2
This is the algebraic expression inside the parentheses. We must now take
the negative 3rd power of this result.
(a^3*b^2)^3 = a^9*b^6
( 4x-y= 2
2x+9y= -12)
B) y=-1/2x+3
C) y=-2x+6
D) y=-2x+3
Answer:
40
Step-by-step explanation:
Answer:
40
Step-by-step explanation: